EKSISTENSI OTONOMI PEMERINTAHAN DESA BERDASARKAN UNDANG-UNDANG NEGARA REPUBLIK INDONESIA NOMOR 6 TAHUN 2014 TENTANG DESA - Herlina, Herlina (Katalogis, 2017)
This writing wants to know what the legal problematics faced in implementing village autonomy based on the Law of the Republic of Indonesia Number 6 Year 2014 About the village, through the method of normative, found things as follows ; Problems of law encountered in implementing village autonomy based on the Law of the Republic of Indonesia Number 6 Year 2014 About the Village, among others; 1) The naming of indigenous villages are different so that the need for uniformity in the naming of indigenous villages; 2) In terms of the organization of village finances, oversight of the implementation of village finances are still weak, so misappropriation of village funds is still a lot going on; 3) The term of office of the village head quite long so it will give birth to "little kings" in the village; 4) In terms of implementation, the placement of the device at least 30 percent of rural women in the village have not been implemented consistently so that just made the object settings, not as subject to the aspirations of the women in the village are not channeled; 5) employment status of the village are not uniform, which the village secretary of civil servants (PNS) while other village officials are not civil servants that government intervention supradesa against the village remains large through the hands of the secretary of the village.